Evaluation of immunity and protection induced in pullets by the V4 oral vaccine against a pneumotropic velogenic Newcastle disease virus (NDV) strain - Gummow, Bruce (University of Pretoria, 2013)
Dissertation (MMed Vet (Poultry diseases))--University of Pretoria, 2002.